Pengaruh Pengaruh Etos Kerja, Locus Of Control Dan Beban Kerja Terhadap Kinerja Pegawai Di Komisi Pemilihan Umum Kota Probolinggo - Anjaksana, Fila; Elmas, Muhammad Syarif Hidayatullah; Dhany, Umi Rahma (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
This research was conducted with the aim to examine the influence of work ethic, locus of control and workload partially on employee performance at the Probolinggo City General Election Commission. The population in this study were employees of the Probolinggo City General Election Commission. 54 employees. The number of samples in this study was 54 employees of the Probolinggo City General Election Commission. In this study the sample size used a saturated sampling technique. Data collection methods in this research are questionnaires, documentation. The research instrument uses a Likert scale. The data sources used in this research are primary data and secondary data. Data analysis methods used in this research are validity test, reliability test, classic assumption test (normality test, multicollinearity test, heteroscedasticity test), multiple linear regression analysis test, coefficient of determination test, partial test (t test). The results of the research show that the Work Ethic variable (X1) has a positive and significant effect on Employee Performance (Y), the Locus of Control variable (X2) has a positive and significant effect on Employee Performance (Y) and the Workload variable (X3) has a positive and significant effect on Employee Performance (Y).